The Effect Guided Discovery-Based Thermochemistry Module on Critical Thinking Skills of High School and Vocational Students - Ratna Sawitri; Sri Mulyani*; Sri Retno Dwi Ariani (Universitas Syiah Kuala, 2023)
Critical thinking is a vital skill for success in higher education and the workforce. However, it is often inadequately emphasized in high school curricula, resulting in students lacking proficiency. Guided discovery-based modules provide a promising approach to enhancing critical thinking by fostering independent exploration and concept discovery. This study aimed to assess the effectiveness of a developed module in improving thermodynamics-related critical thinking skills among 10th-grade students in Boyolali Regency, Indonesia. Five schools were randomly selected, with two classes from each forming control and experimental groups. The experimental group utilized the developed module, while the control group used traditional textbooks. Validated by experts, a test was administered to evaluate students' critical thinking skills, and statistical analysis revealed a significant difference between the experimental and control groups. The developed module demonstrated superior efficacy in enhancing critical thinking skills compared to traditional textbooks. Variations in mean scores among the schools suggest the need for further investigation across diverse educational contexts. The study's outcomes have implications for teaching and learning in Indonesia and other countries where critical thinking is insufficiently emphasized in high school curricula. Ethical considerations were upheld, ensuring participant rights and confidentiality. Future research can explore the module's effectiveness in improving critical thinking across different subjects and educational settings